2009
DOI: 10.1038/sj.bjc.6605056
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of RET somatic mutations with clinicopathological features in sporadic medullary thyroid carcinomas

Abstract: Screening of REarranged during Transfection (RET) gene mutations has been carried out in different series of sporadic medullary thyroid carcinomas (MTC). RET-positive tumours seem to be associated to a worse clinical outcome. However, the correlation between the type of RET mutation and the patients' clinicopathological data has not been evaluated yet. We analysed RET exons 5, 8, 10 -16 in fifty-one sporadic MTC, and found somatic mutations in thirty-three (64.7%) tumours. Among the RET-positive cases, exon 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
124
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(142 citation statements)
references
References 36 publications
(60 reference statements)
8
124
1
2
Order By: Relevance
“…We know that the presence of RET somatic mutations correlates with an advanced stage at the time of diagnosis and a lower survival rate (11,12,13). In the present series, the RET somatic mutations did not correlate with the death of these patients.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…We know that the presence of RET somatic mutations correlates with an advanced stage at the time of diagnosis and a lower survival rate (11,12,13). In the present series, the RET somatic mutations did not correlate with the death of these patients.…”
Section: Discussionmentioning
confidence: 41%
“…Advanced age at diagnosis, advanced stage of the disease and, in particular, the presence of distant metastasis at the time of diagnosis have been found to be correlated with a worse prognosis (6,7,8,9). RE-arranged during transfection (RET) somatic mutations, which are present in 40-50% of sporadic MTC patients, have also been recognized as a poor prognostic factor for the outcome of these patients (10,11,12,13).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, somatic RET mutations and/or RET polymorphisms were analyzed in several series of sporadic MTC, and RET status was found to correlate with patient outcome (10)(11)(12). Recent reports have demonstrated that somatic RET mutations occur in 30-50% of sporadic cases of MTC, and they are a negative predictor of cancer remission and survival (13)(14)(15). Such reports were not always homogeneous in terms of the frequency, type, and site of somatic RET mutations, or their association with clinical and pathological features, suggesting that other biological markers could also be useful for ascertaining a patient's risk.…”
Section: Introductionmentioning
confidence: 99%
“…In Portugal and Czech Republic, the most common mutation was codon 918 for the sporadic form of MTC (Zedenius et al, 1994). In USA the most common mutation in this gene was at codon 634 in patients with hereditary MTC (Moura et al, 2009). In Iran and China also the highest genetic variation and mutation was reported at codon 634 (Zhou et al, 2007;Hedayati et al, 2011).…”
Section: Discussionmentioning
confidence: 99%